Factors Contributing to Antenatal Care and Delivery Practices in Village Development Committees of Ilam District, Nepal (Kathmandu University Medical Journal, 2014)
Background Proper antenatal care and good delivery practice helps to prevent the complications of childbirth and ensures a wholesome maternal and child health in the future. Almost half of the births in the developing countries take place without a skilled birth attendant. Objectives To assess the antenatal care (ANC) and delivery practices in the Village Development Committees (VDC) of Ilam district, Nepal and to identify the relationship with the socio-demographic factors. Method Cross sectional study of 262 mothers of reproductive age group having at least one child of less than five years of age, selected by simple random sampling, was carried out over different VDCs of Ilam by face to face interview using semi-structured questionnaire. Results Among 262 mothers, 34.7% were married before the age of 18 years. 69.5% of the mothers had attended four antenatal care visits. Nearly 47% of the deliveries were conducted at home out of which only 33.6% were conducted by skilled birth attendant. Number of children and maternal education were found to significantly affect the ANC visit and place of delivery. Age at marriage and age at first pregnancy were significantly associated with the place of delivery. Conclusion Large proportion of mothers still do not have adequate antenatal visits and this is supported by the fact that nearly half of the deliveries were conducted at home. Motivation and incentives are required for pregnant mothers especially in rural areas regarding importance of adequate antenatal visits and delivery in health institutions. Population policies should be aimed at reducing proportion of women marrying and giving birth in their teens. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11029 Kathmandu University Medical Journal Vol.11(1) 2013: 60-65